Regulatory T-cells and associated pathways in metastatic renal cell carcinoma (mRCC) patients undergoing DC-vaccination and cytokine-therapy. - Adrian Schwarzer (Public Library of Science (PLoS), 2012)
Purpose To evaluate CD4(+)CD25(+)FOXP3(+) T regulatory cells (T(REG)) and associated immune-regulatory pathways in peripheral blood lymphocytes (PBL) of metastatic renal cell carcinoma (mRCC) patients and healthy volunteers. We subsequently investigated the effects of immunotherapy on circulating T(REG) combining an extensive phenotype examination, DNA methylation analysis and global transcriptome analysis. Design Eighteen patients with mRCC and twelve volunteers (controls) were available for analysis. T(REG) phenotype was examined using flow cytometry (FCM). T(REG) were also quantified by analyzing the epigenetic status of the FOXP3 locus using methylation specific PCR. As a third approach, RNA of the PBL was hybridized to Affymetrix GeneChip Human Gene 1.0 ST Arrays and the gene signatures were explored using pathway analysis. Results We observed higher numbers of T(REG) in pre-treatment PBL of mRCC patients compared to controls. A significant increase in T(REG) was detected in all mRCC patients after the two cycles of immunotherapy. The expansion of T(REG) was significantly higher in non-responders than in responding patients. Methylation specific PCR confirmed the FCM data and circumvented the variability and subjectivity of the FCM method. Gene Set Enrichment Analysis (GSEA) of the microarray data showed significant enrichment of FOXP3 target genes, CTLA-4 and TGF-ß associated pathways in the patient cohort. Conclusion Immune monitoring of the peripheral blood and tumor tissue is important for a wide range of diseases and treatment strategies. Adoption of methodology for quantifying T(REG) with the least variability and subjectivity will enhance the ability to compare and interpret findings across studies.